2019
DOI: 10.1016/j.jaip.2018.10.032
|View full text |Cite
|
Sign up to set email alerts
|

A 1-Day, 90-Minute Aspirin Challenge and Desensitization Protocol in Aspirin-Exacerbated Respiratory Disease

Abstract: Background: Aspirin challenge and desensitization remains the gold standard in diagnosis and treatment for patients with aspirin-exacerbated respiratory disease (AERD), but the protocols can be time and resource intensive. Objective: To provide evidence that oral aspirin challenge and desensitization can be safely performed in an outpatient setting in one day. Methods: Forty-four patients with a confirmed diagnosis of AERD, stable asthma and baseline FEV1 ≥70% of predicted, completed an oral aspirin challenge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 12 publications
0
37
0
Order By: Relevance
“…New ASA challenge protocols are continuing to be developed and increase the efficiency of diagnosis. For example, DeGregorio et al recently demonstrated that a one-day ASA challenge utilizing a 90-min dose escalation protocol at a starting dose of 40.5 mg was effective in desensitizing AERD patients with stable asthma and baseline FEV-1 greater than or equal to 70% [53].…”
Section: Diagnostic Workupmentioning
confidence: 99%
“…New ASA challenge protocols are continuing to be developed and increase the efficiency of diagnosis. For example, DeGregorio et al recently demonstrated that a one-day ASA challenge utilizing a 90-min dose escalation protocol at a starting dose of 40.5 mg was effective in desensitizing AERD patients with stable asthma and baseline FEV-1 greater than or equal to 70% [53].…”
Section: Diagnostic Workupmentioning
confidence: 99%
“…Aspirin desensitizations were conducted using a single-day oral challenge protocol. 10 Reasons for more than 1 aspirin desensitization included an intervening pregnancy or surgery that required stoppage of aspirin. Subjects with incomplete spirometry data were excluded.…”
Section: To the Editormentioning
confidence: 99%
“…Regimens with shorter dosage intervals (1 to 1.5 hours), a larger starting dose of aspirin (40 mg), and a higher rate of dose escalation have been used for the procedure. They were shown to have similar safety and tolerance profiles; therefore, they can be readily applied in clinical settings 4546. On the other hand, only aspirin OPT can be performed in patients with aspirin/NSAID-induced cutaneous manifestations.…”
Section: Diagnostic Approach For Patients With Nsaid Hypersensitivitymentioning
confidence: 99%
“…A modified protocol for aspirin challenge and desensitization was suggested by the EAACI 2019 guideline, consisting of 2 days of ATAD 46. The 1-day ATAD protocol proposed by DeGregorio, et al45 provides a quick alternative for busy patients. Details and time schedules of the two protocols are shown in Table 1.…”
Section: Treatmentmentioning
confidence: 99%